IGLESIA Y POLÍTICA EN CÓRDOBA: LA BÚSQUEDA DE UNA SOCIEDAD CATÓLICA - Moyano, Sara Alejandra (2011)
The purpose of this paper is to analyze the relationship between the provincial government of the dictatorship of 1966-1973 (known as “Revolución Argentina”) and the Catholic Church in Córdoba during the period 1969-1973. This paper seeks to qualify the traditional interpretations of the relationship between the institutional church and politics, who have argued that  this institution legitimized de facto governments. While we believe that there was legitimation, here we attempt to contribute some elements that help to clarify the ways in which it took place and the interests that promoted it. This means including the divisions and tensions within the Catholic field in Córdoba, since the emergence of renovating currents, linked to Vatican II.